Mechanisms for Improving Hepatic Glucolipid Metabolism by Cinnamic Acid and Cinnamic Aldehyde: An Insight Provided by Multi-Omics - Wu, You; Wang, Ming-hui; Yang, Tao; Qin, Tian-yu; Qin, Ling-ling; Hu, Yao-mu; Zhang, Cheng-fei; Sun, Bo-ju; Ding, Lei; Wu, Li-li; Liu, Tong-hua (Frontiers in Nutrition, 2022)
Cinnamic acid (AC) and cinnamic aldehyde (AL) are two chemicals enriched in cinnamon and have been previously proved to improve glucolipid metabolism, thus ameliorating metabolic disorders. In this study, we employed transcriptomes and proteomes on AC and AL treated db/db mice in order to explore the underlying mechanisms for their effects. Db/db mice were divided into three groups: the control group, AC group and AL group. Gender- and age-matched wt/wt mice were used as a normal group. After 4 weeks of treatments, mice were sacrificed, and liver tissues were used for further analysis. Functional enrichment of differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) was performed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. DEPs were further verified by parallel reaction monitoring (PRM). The results suggested that AC and AL share similar mechanisms, and they may improve glucolipid metabolism by improving mitochondrial functions, decreasing serotonin contents and upregulating autophagy mediated lipid clearance. This study provides an insight into the molecular mechanisms of AC and AL on hepatic transcriptomes and proteomes in disrupted metabolic situations and lays a foundation for future experiments.